Lumen diameter variation of hand radial artery in cadaver anatomical snuffbox - Leonardo Lubis; Gita Tiara Dewi Nasution; Adilla Zulfana Hermawan (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2021)
Background: The most recent finding in interventional cardiology is